2015
DOI: 10.1002/rcs.1692
|View full text |Cite
|
Sign up to set email alerts
|

Toward teleoperated needle steering under continuous MRI guidance for prostate percutaneous interventions

Abstract: The feasibility of teleoperated bevel-tip needle steering using the proposed system was shown in a phantom experiment. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In the case of a continuous insertion whose velocity control is left to the surgeon, the robot motion is often limited to the insertion and rotation around the needle axis [12], [13], [10]. Continuous needle insertion usually requires the use of US imaging to obtain a fast visual feedback and automatic needle insertion under 2D or 3D US guidance have been the focus of many work [5], [14], [15], [16].…”
Section: A Related Workmentioning
confidence: 99%
“…In the case of a continuous insertion whose velocity control is left to the surgeon, the robot motion is often limited to the insertion and rotation around the needle axis [12], [13], [10]. Continuous needle insertion usually requires the use of US imaging to obtain a fast visual feedback and automatic needle insertion under 2D or 3D US guidance have been the focus of many work [5], [14], [15], [16].…”
Section: A Related Workmentioning
confidence: 99%
“…The robot is controlled through a joystick without force feedback located in the control room. Seifabadi et al demonstrated the feasibility of using fiber Bragg grating (FBG) sensors to measure the force and provide force feedback to the user operating an MR compatible robot [15]. The most important challenge towards force feedback in MR-guided tele-operated interventions is the lack of a reliable MR-compatible force sensor.…”
Section: Haptic Interfacementioning
confidence: 99%
“…In radioactive tumor brachytherapy surgery, radioactive seeds implantation can adversely affect the operator's health and the potential ill effects of radiation cannot be ignored [23][24][25][26][27][28]. The robot assisted puncture system could provide great convenience for doctor once it can automatically perform needle puncture, radioactive seeds delivery and keep the doctor at a safe distance from the radioactive seeds.…”
Section: Introductionmentioning
confidence: 99%